Pola Resistensi Bakteri Terhadap AntibiotikPada Penderita Pneumonia Di Rsup Dr. Soeradji Tirtonegoro Klaten Periode Agustus 2013-Agustus 2015 - Sulistyaningrum, Ratnaningtyas; , Prof. Dr. M. Kuswandi, SU., M.Phil., Apt; , Ratna Yulia, M. Biotech. St (2016)
Pneumonia is one of the acute respiratory infection caused by microorganisms in the end of bronhiolus and alveoli. The use of broad-spectrum antibiotics to treat pneumonia too often increases the resistance of bacteria to antibiotics so antibiotics should be used based on the resistance patterns of bacteria that causes pneumonia. The purpose of this study was to determine the pattern of bacterial resistance to antibiotics as well as the appropriateness of use of antibiotics based on the results of bacteria sensitivity test in patients with pneumonia in Dr. Soeradji Tirtonegoro Hospital Klaten between August 2013 and August 2015. This study was a non-experimental study with retrospective data collection in patients with pneumonia in Dr. Soeradji Tirtonegoro Hospital Klaten between August 2013 and August 2015 and analyzed descriptively. The data collected was the data of culture and bacteria sensitivity test results to antibiotics as well as data on the use of antibiotics in patients with pneumonia. The results showed that most pneumonia-causing bacteria isolated from sputum and blood specimens in 40 patients with pneumonia in Dr. Soeradji Tirtonegoro Hospital Klaten between August 2013 and August 2015 was Pseudomonas sp and Staphylococcus epidermidis with a percentage of 12,91%. Resistance patterns showed that the Pseudomonas sp were resistant to amoxicillin clavulanic acid and ampicillin (87,5%), cefixime (75%), gentamicin (75%), cotrimoxazole (62,5%), and ciprofloxacin (50%). Staphylococcus epidermidis were resistant to ampicillin, cefixim, cotrimoxazol with a percentage of 87,5%, gentamicin, and ciprofloxacin (62,5%). The results of the analysis of appropriateness of definitive antibiotics showed that 52,64% of antibiotics were given in accordance with the culture results, sensitivity test, as well as antibiotic spectrum activity. Keywords: resistance, antibiotics, pneumonia